Carotenoid diversity in 22 species of Malay traditional ulam - Othman, Rashidi; Mohd Hassan, Norazian; Mohd Zaifuddin, Fatimah Azzahra (2012)
There has been renewed interest of discovering sources of antioxidants that could help in preventing or controlling the occurrence of many chronic illness especially for the ones related to oxidative damages caused by free-radicals. These antioxidants including the yellow-orange-red pigments, collectively known as carotenoids, which some of them play vital role as pro-vitamin A that supples humans' skin and visual health. Carotenoids also act as boosters to our immune system. Interestingly, although they are yellow-to-red in colours, carotenoids are found in greater concentration in dark green leaves. Due to its location in the vicinity of the equator, Malaysia is blessed with wonderful diversity of evergreen plants yet documentation for their carotenoids' accumulation is still lacking.